The Relationship Between Patterns of Care and Level of Emotional Intelligence Among Pre-School Children - Farida, Farida (Journal of Global Research in Public Health, 2020)
Psychologists Salovy from Harvard University and Mayer from the University of New Hampshire reveal that emotional intelligence is an emotional quality that is important for a successful life. These qualities include empathy, expressing and understanding feelings, controlling anger, independence, ability to adapt, to be liked, ability to solve interpersonal problems, perseverance, solidarity, friendliness and respect. Factors that can affect emotional intelligence include psychological factors, emotional training factors and family education factors. The purpose of this study was to determine the relationship between parenting style and the level of emotional intelligence of preschool children. The research design used was cross-sectional, the research was carried out at TK Kemala Bhayangkari 48 Tulungagung, The results showed that respondents who received authoritative care were 16 children (53.3%) who all had emotional intelligence, including in the smart category. Meanwhile, none of the children who received authoritative care were in the less intelligent category. The results of the Chi-Square statistical test showed that p = 0.000 <α = 0.05, which means that there is a relationship between parenting styles and the level of emotional intelligence of preschool children. It is concluded that different parenting styles will produce children with different levels of emotional intelligence. The better the parenting method, the better the level of intelligence of a child. Recommendations for future researchers are expected to further investigate the factors that can influence the individual characteristics of parents and the level of emotional intelligence of preschool children.